PENGARUH PENGISI HASIL SPRAY DRYING TERHADAP KARAKTERISTIK ORALLY DISINTEGRATING TABLET (ODT) FAMOTIDIN - Faizatun, Faizatun; Saputra, Andreas Agung; Nafisa, Safira (Jurnal Farmasi Indonesia, 2019)
Famotidine is used in the treatment of gastric disease and required rapid action of drugs in application. Orally Disintegrating Tablet (ODT) dosage has a fast disintegration time, caused therapeutic effects of famotidine could occur immediately. In this study, a characteristics of ODT comparison is made with ODT diluent with spray drying methods and comparative diluent in the market. ODT diluent consisted of Avicel PH 102, xylitol, mannitol, and crospovidone (2, 3.5, 5%). ODT diluent is used for the manufacture of ODT tablets with direct compresstion method. Evaluation of diluent consisted of water content, flowcity, and compressibility test, while evaluation of ODT tablets consisted of disintegration time, dissolution, hardness, and friability to see the effect of differences crospovidone concentration. Based on the result, F III with 5% crospovidone concentration had a faster disintegration time (44.45 seconds), smaller hardness (5.68 kg / cm2) and greater friability (0.46%) than F I and F II tablets. F III tablet has a longer disintegration time (44.45 seconds) than comparable ODT tablets (33 seconds).